Schlesische Dialektismen im Roman „Die Verwandelten“ von Ulrike Draesner - Iryna Mykytiuk (Linguistische Treffen in Wrocław, 2025)
This paper examines the literary treatment of trauma and memory in Ulrike Draesner’s novel “Die Verwandelten” focusing on the use of Silesian dialectics as expressive tools for conveying traumatic experiences. The aim of this study is to explore how dialectisms act as narrative strategies to represent trauma and articulate the linguistic experiences of the characters. The methodological foundation of the analysis is based on the approaches of memory studies and trauma studies, as well as sociolinguistic concepts such as multilingualism and the linguistic experience of trauma. The analysis reveals that dialectisms not only convey regional authenticity but also serve as a medium to depict the fragmented perception and fractured identity of the characters. The study demonstrates that through the deliberate use of Silesian dialectisms, Ulrike Draesner creates literary tension surrounding issues of trauma, violence, loss of homeland and language. This research analyzes how Silesian dialectisms act as a unique space of memory and a means of identity exploration within the novel. By incorporating dialectisms, Draesner effectively portrays the complexity of individual and collective experiences in the context of displacement, exile, and transgenerational trauma. The findings of this analysis contribute to a deeper understanding of the role of language and dialect in the literary representation of trauma.